Manhaj Sastera Islam Menurut Kaca Mata Shaykh Abu al-Hasan ‘Ali al-Nadwi - Mohd Shahrizal, Nasir (2011)
This article is dedicated to discussing the aspirations and views of AbË al-Hasan ÑAlÊ al-NadwÊ, the founder of the Universal League of Islamic Literature, on the Islamic literature framework in an attempt to rectify assumptions and misconceptions on Islamic literature. Islamic literature has been assumed by many as obsolete, rigid and untangable for the fact that it is committed to the religious, value-orientation and ethical commitments in accordance to the Islamic worldview. This article highlights the meaning of Islamic literature and its concept based on al-NadwÊ point of view. Al-NadwÊ is a well-known scholar in promoting Islamic literature as an intellectual means of enlightenment to society. Without any doubt, al-NadwÊ was contribute such a great contribution to the cultural and literature studies of Islam.